2012
DOI: 10.1021/jf303515z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic Acid Production in the Processing of Cabbage Leaves

Abstract: Lysophosphatidic acid (LPA) is a lipid mediator involved in various physiological responses, including wound healing. Evidence of the antiulcer activity of LPA has been reported, and soybean LPA at a concentration of 10 μM is effective in reducing stress-induced gastric ulcer. Because LPA can be formed from phosphatidic acid (PA) by digestive phospholipase A₂, dietary PA can be considered a potential antiulcer phospholipid. In this study, PA production in cut processing of cabbage leaves was examined. The amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Cabbage is known to contain abundant PLD activity [17]. The PLD activity converts endogenous phospholipids to phosphatidic acid when raw leaves are homogenized [18]. In fact, cabbage lipids extracted from raw leaves contain much more phosphatidic acid than lipids from boiled leaves ( Fig.…”
Section: Formation Of Pc1p In Cabbage Homogenatesmentioning
confidence: 99%
“…Cabbage is known to contain abundant PLD activity [17]. The PLD activity converts endogenous phospholipids to phosphatidic acid when raw leaves are homogenized [18]. In fact, cabbage lipids extracted from raw leaves contain much more phosphatidic acid than lipids from boiled leaves ( Fig.…”
Section: Formation Of Pc1p In Cabbage Homogenatesmentioning
confidence: 99%
“…PA Content in Boiled and Non-boiled Cereals. Previously, we showed that cutting or mashing of raw cabbage leaves induced PA formation in the leaves, 20 which was caused by hydrolysis of endogenous phospholipids, including PC by activated phospholipase D (PLD) during tissue destruction. Consistent with our previous findings, levels of PA prepared from boiled cabbage leaves, radish roots, and carrot roots were low relative to those prepared from raw ones.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Laser light scattering and multi size coulter counter other than instrumental methods, which can be used for the characterization of size, shape and morphology of the microspheres. 50…”
Section: Particle Size and Shapementioning
confidence: 99%